Analisis Dampak Game Online Dalam Pembentukan Karakter Siswa MIN 3 Kota Lhokseumawe - Haliza Ritonga; Barus, Jumat; Ma'awiyah, Aisyah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This study aimed to analyze the effect of online games on students’ character development at MIN 3 Lhokseumawe. The research employed quantitative causal-correlational research. The population consisted of all fifth and sixth grade students at MIN 3 Lhokseumawe, totaling 124 students. The sample was selected through purposive sampling based on the criterion of students who actively played online games, resulting in 30 students as research participants. Data were collected using a questionnaire that measured the intensity of online game usage and students’ character dimensions, including religious character, tolerance, discipline, creativity, and reading interest. The data were analyzed using descriptive statistics, prerequisite tests, and simple linear regression with the assistance of SPSS version 21. The results indicated that online games had a significant effect on students’ character development. This was evidenced by the value of tcount being higher than ttable (8.108 > 2.045) and a significance value of 0.000 < 0.05. The coefficient of determination showed that online games contributed 70.1% to the variation in students’ character development. The findings suggested that high intensity of online game playing tended to be associated with less positive character development, particularly in terms of religiosity, tolerance, discipline, creativity, and reading interest. Therefore, this study highlights the importance of monitoring and managing online game usage as part of efforts to strengthen character education in the digital era, particularly at the Islamic elementary school level.